Pan-Canadian asthma and COPD standards for electronic health records: A Canadian Thoracic Society Expert Working Group Report. Issue 4 (2nd October 2018) - Lougheed, M. Diane; Taite, Ann; ten Hove, Julia; Morra, Alison; Van Dam, Anne; Ducharme, Francine M.; Ferrone, Madonna; Gershon, Andrea; Goodridge, Donna; Graham, Brian; Gupta, Samir; Licskai, Christopher; et al.
Abstract: RATIONALE: The Canadian Thoracic Society established a pan-Canadian respiratory standards initiative for electronic health records (EHRs) (PRESTINE). OBJECTIVE: We aimed to identify and define respiratory data elements for EHRs for asthma, COPD and related pulmonary function elements that enable adherence with respiratory best practice guidelines. METHOD: Potential data elements (n = 425) were based on a published asthma/COPD information model. Using modified RAND-UCLA Appropriateness and Delphi methods, a working group (WG) of 12 experts independently rated each element based on 4 domains (strength of evidence, clarity, relevance, feasibility) using a 5-point Likert Scale, plus an overall rating (include as core, optional or exclude). Subsequent independent voting rounds addressed elements lacking consensus (defined as 60% agreement) in previous rounds. A facilitated face-to-face meeting was convened during which WG consensus was sought. A list of included data element definitions and medications were sent for external stakeholder review. MAIN RESULTS: After 4 rounds of voting (including the face-to-face meeting), the WG identified 77 core and 23 optional elements for asthma, and 72 core and 21 optional elements for COPD. Of those, 53 core and 15 optional elements were common to both asthma and COPD. The list of asthma/COPD and smoking cessation medications included 40 products and 48 brands. CONCLUSIONS: This consensus initiative has identified asthma, COPD, and pulmonary function data elements and definitions as well as a list of medications recommended by experts for inclusion in EHRs to support primary and tertiary care for these diseases, and to enable outcomes monitoring, benchmarking and performance evaluation.